Productivity of Salt Farmers in East Java Province - Chasanah, Uswatun; Prasetiyo, Didit Eko (Indonesian Journal of Entrepreneurship and Startups, 2025)
Indonesia is a maritime country with the second-longest coastline in the world after Canada. With vast seas and year-round sunshine, Indonesia has three main factors for salt production: seawater, coastline and sunshine. However, despite its huge potential, Indonesia continues to import salt. This study aims to assess the productivity of salt farmers in East Java. The study used secondary data from relevant agencies. The results show that the productivity of salt farmers in East Java in 2020 is 17,937.169 kg/person. However, local production is only able to fulfill about 20% of the total salt demand in East Java. This low fulfillment is caused by several factors, including erratic weather, limited land, and the number of workers